A method for preparing dolomite powder coated with nano-oxide

By preparing the white cloud stone powder covered by nano oxide, the problem of lack of dispersion of nano metal oxides, achieve a more efficient anti -mold and antibacterial effect, reduce production costs, and improve the stability of the covering particles.

CN117361924BActive Publication Date: 2025-01-28SHANXI OUBEIMU NANO TECH CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202311216842.6
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-09-20
Publication Date
2025-01-28
Estimated Expiration
2043-09-20

AI Technical Summary

Technical Problem

In the prior art, the dispersion of nanometal oxides in the carrier material is insufficient, resulting in the need to increase the amount of addition to ensure the anti-mold and sterilization effect, which increases the production cost, and the commonly used dispersant is large in use, troublesome in handling, and has a large environmental pollution. .

Method used

By preparing white clouds covered by nano oxide, the hardness and surface characteristics of white cloud stone powder are used to combine the coupling agent and dispersant to improve the decentralization and binding strength of nano oxides to reduce the reunion of nano oxides.

Benefits of technology

Improved the decentralization of nano oxides, reduced the use of nano oxides, reduced production costs, enhanced the effect of anti -mildew and antibacterial effects of carrier materials, and due to the hardness and stability of white cloud stone powder, it improved the stability of the covered particles sex.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN117361924B_ABST
    Figure CN117361924B_ABST
Patent Text Reader

Abstract

The invention discloses a method for preparing dolomite powder coated with nano-oxide, belonging to the technical field of nano-oxide modification and treatment, and is prepared from the following raw materials in weight percentage: 80% to 85% dolomite powder, 10% to 18% nano-oxide, 1% to 5% coupling agent, and 0.5% to 1.5% dispersant. The surface layer of the product produced by using the dolomite powder coated with nano-oxide provided by the invention is dense, the content of nano-oxide is higher, the surface layer of the product does not have the conditions for mold growth, and can more effectively play the role of mildew and antibacterial. The method for preparing dolomite powder coated with nano-oxide provided by the invention does not require a high temperature environment, the production conditions are easy to achieve, the agglomeration of nano-oxide is avoided, the coupling agent will not be carbonized due to high temperature, and the performance of the coated particles is guaranteed.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a method for preparing dolomite powder coated with nano-oxides, and belongs to the technical field of nano-oxide modification treatment. Background Art

[0002] Nanopowders have special properties that are significantly different from bulk materials due to their extremely small size. For example, some nanometal oxides have long-lasting bactericidal and antibacterial effects. When added to carrier materials such as marble, plastic, plate, and coating, the carrier materials can have anti-mildew and antibacterial functions, thereby improving the performance of the carrier materials. On the one hand, the properties of nanopowders strongly depend on the size, morphology, and microstructure of nanoparticles; on the other hand, nanoparticles have a large specific surface area and high surface energy, and are prone to particle agglomeration during application, resulting in the loss of the physical properties of nanoparticles. Therefore, the dispersibility of nanometal oxides in carrier materials greatly affects their use effect. In order to ensure the anti-mildew and antibacterial effect of the carrier material, it is usually necessary to increase the amount of nanometal oxide added, resulting in increased production costs. At present, the method for improving the dispersibility of nanopowders is mainly to use surface modification technologies such as dispersants and surfactants. The amount of modifiers used is large, the handling is troublesome, and the environmental pollution is large. The present invention aims to provide a new method to solve the dispersibility problem of nanometal oxides.

[0003] It should be noted that the above contents belong to the technical knowledge of the inventor and do not necessarily constitute prior art. Summary of the invention

[0004] In order to solve the problems existing in the prior art, the present invention provides a method for preparing dolomite powder coated with nano-oxides, which improves the dispersibility of the nano-oxides, and the dolomite particles have high hardness and no fine cracks inside, thereby reducing the defects of the coated particles and improving the stability of the coated particles.

[0005] The present invention achieves the above-mentioned purpose by adopting the following technical solutions:

[0006] A method for preparing dolomite powder coated with nano-oxides, which is prepared from the following raw materials by weight: 80% to 85% dolomite powder, 10% to 18% nano-oxides, 1% to 5% coupling agent, and 0.5% to 1.5% dispersant;

[0007] Among them, the nano-oxide is selected from any one or more of copper oxide, zinc oxide, magnesium oxide, aluminum oxide, titanium oxide, and silver oxide. The types of sterilization can be broadened by compounding different nano-oxides.

[0008] The coupling agent is composed of component A and component B, the weight ratio of component A to component B is 1:1 to 1:3, component A is selected from any one or two of stearic acid and malic acid, and component B is selected from any one or two of silane coupling agent and aluminate coupling agent; preferably, the R group in the silane coupling agent YR-SiX3 is preferably a short-chain alkane.

[0009] The dispersant is selected from one or both of gum arabic and sodium alkylbenzene sulfonate.

[0010] Optionally, the blue light whiteness of the dolomite powder is 60-80.

[0011] Among them, each coupling agent is used after the purchased stock solution is diluted 10 to 20 times with water; each dispersant is used after the purchased powder is dissolved after adding 1:15 to 1:20 weight multiple of water.

[0012] Dolomite powder is alkaline, while component A, which constitutes the coupling agent, is acidic. Therefore, component A can be used to form micro-pits on the surface of dolomite particles through acid etching for the embedding of nano-oxides; component B, which constitutes the coupling agent, can further activate the active sites on the surface of dolomite particles; components A and B cooperate with each other to improve the bonding strength between nano-oxides and dolomite particles.

[0013] In a preferred embodiment of the present invention, the particle shape of the dolomite powder is approximately spherical, olive-shaped or columnar, and has a large surface area for compounding with the nano-oxide. The resulting dolomite powder coated with the nano-oxide has high dispersibility.

[0014] In a preferred embodiment of the present invention, the particle size of dolomite powder is 800-1200 mesh; the particle size of nano-oxide is 1-100 nm.

[0015] In a preferred embodiment of the present invention, dolomite powder is taken from Yu County, Yangquan, Shanxi Province, and the proportions of the ingredients contained in the dolomite powder are: 5% to 10% silicon dioxide, 25% to 32% calcium oxide, 15% to 21% magnesium oxide, less than 3% aluminum oxide, less than 1% iron oxide, and 5% to 8% acid insoluble matter. Silicon dioxide has a high hardness, and its appropriate proportion in the dolomite powder ensures the hardness of the dolomite powder, and the dolomite powder formed by nano-oxide coating has high weather resistance.

[0016] The method for preparing the dolomite powder coated with nano-oxide provided by the present invention comprises the following steps:

[0017] (1) grinding dolomite powder by a vertical mill and then selecting ultrafine dolomite powder with a particle size of 800 to 1200 mesh by air separation;

[0018] (2) adding water to dolomite powder, part of the dispersant and coupling agent A, and dispersing them uniformly at high speed to prepare a dolomite powder suspension with a solid content of 20 to 30 wt %;

[0019] (3) adding water to the nano-oxide and the remaining dispersant, and then dispersing them uniformly at high speed to prepare a nano-oxide suspension having a solid content of 20 to 30 wt %;

[0020] (4) adding water to the dolomite powder suspension, the nano-oxide suspension and the coupling agent B, and stirring at a low speed to prepare a mixed suspension, wherein the pH value of the mixed suspension is 6.5 to 7.5, preferably 6.5 to 7.0;

[0021] (5) Drying the mixed suspension obtained in step (4) at a temperature below 35° C. to prepare dolomite powder coated with nano-oxide.

[0022] Wherein, the amount of the dispersant used in step (2) is 80% to 90% of the total weight of the dispersant.

[0023] In steps (4) and (5), not only the dispersant is used to fully disperse the dolomite powder and the nano-oxide, but also the dolomite particles and the nano-oxide particles rub against each other during the dispersion process, thereby improving the particle shape and making the particle shape tend to be spherical, and stimulating and activating the emergence of new interfaces, thereby increasing the surface activity of the dolomite particles and the nano-oxide particles, and facilitating the coating and compounding of the two.

[0024] In a preferred embodiment of the present invention, in step (1), during air selection, the passing rate of dolomite powder through 800 mesh sieve is 100%, the passing rate of 950 mesh sieve is 75%±5%, the passing rate of 1100 mesh sieve is 40%±5%, and the passing rate of 1200 mesh sieve is less than 5%. The particle size of dolomite powder is distributed through the above-mentioned gradation, so that the gaps between the particles can be fully filled and the void ratio can be reduced. The surface layer of the product filled and produced by the dolomite powder coated with nano-oxide provided by the present invention is more dense, and the content of nano-oxide is higher, so that the surface layer of the product does not have the conditions for mold growth, and the anti-mildew and antibacterial effect is more effectively exerted.

[0025] In a preferred embodiment of the present invention, in step (2), the dispersion speed when preparing the dolomite powder suspension is 150,000 to 200,000 rpm, the dispersion time is 30 to 60 min, and the dispersion temperature is not higher than 30°C.

[0026] In a preferred embodiment of the present invention, in step (3), the dispersion speed when preparing the nano-oxide suspension is 80,000 to 120,000 rpm, the dispersion time is 30 to 60 min, and the dispersion temperature is not higher than 30°C.

[0027] In a preferred embodiment of the present invention, in step (4), the mixing method of the dolomite powder suspension, the nano oxide suspension and the coupling agent is: slowly pouring the coupling agent into the dolomite powder suspension, stirring at a speed of 500 to 800 rpm for 5 minutes, and then slowly pouring the nano oxide suspension, stirring at a speed of 1000 to 1500 rpm for 30 minutes.

[0028] In a preferred embodiment of the present invention, when the dolomite powder coated with nano-oxide is used as a filler in the preparation of artificial marble, plastic profiles, and wood composite panels, the drying method in step (5) is: the mixed suspension is washed with water, filtered or centrifuged, washed with water, and then centrifuged, and then air-dried at a temperature below 35°C.

[0029] In a preferred embodiment of the present invention, when the dolomite powder coated with nano-oxide is used as a filler in the preparation of putty powder, grout, and plaster mortar, the drying method in step (5) is: the mixed suspension is atomized and dried at a temperature below 35°C.

[0030] The beneficial effects of this application include but are not limited to:

[0031] The method for preparing dolomite powder coated with nano-oxides provided by the present invention can evenly coat nano-oxide particles on a micron-sized dolomite particle substrate, thereby avoiding agglomeration of nano-oxides, improving the dispersibility of nano-oxides, enabling nano-oxides to fully exert their mildew and antibacterial activities, reducing the amount of nano-oxides used, and reducing costs; the dolomite particles have high hardness and no fine cracks inside, forming a solid core of the coating material, reducing the defects of the coated particles and improving the stability of the coated particles; after the surface of the dolomite particles is coated with nano-oxides, the edges and corners of the surface of the dolomite particles are further blunted, thereby increasing the fluidity of the coated particles and facilitating dispersion.

[0032] The product produced by using the dolomite powder coated with nano-oxides provided by the present invention has a dense surface layer, a higher content of nano-oxides, and the surface layer of the product does not have the conditions for mold growth, and can more effectively play the role of mildew prevention and antibacterial.

[0033] The method for preparing dolomite powder coated with nano-oxides provided by the present invention does not require a high temperature environment, is easy to achieve production conditions, avoids agglomeration of nano-oxides, and the coupling agent will not be carbonized due to high temperature, thereby ensuring the performance of the coated particles. BRIEF DESCRIPTION OF THE DRAWINGS

[0034] The drawings described herein are used to provide a further understanding of the present application and constitute a part of the present application. The illustrative embodiments of the present application and their descriptions are used to explain the present application and do not constitute an improper limitation on the present application. In the drawings:

[0035] Figure 1This is a model diagram of the coating of nano-oxide particles on the surface of dolomite powder particles;

[0036] Figure 2 The SEM images of nano-oxide particles before and after coating on the surface of dolomite powder particles;

[0037] Figure 3 The anti-mildew test results of putty block sample 1 are shown below;

[0038] Figure 4 The anti-mildew test results of putty block sample 2;

[0039] Figure 5 This is the anti-mildew test result of putty block sample 3. DETAILED DESCRIPTION

[0040] The present invention will be further described in detail in the following content. However, it should be pointed out that the following specific embodiments only provide specific operation examples of the present invention in an exemplary manner, but the protection scope of the present invention is not limited thereto. The protection scope of the present invention is limited only by the claims. It is obvious to those skilled in the art that various other improvements and replacements can be made to the embodiments of the present invention within the protection scope defined by the claims of the present invention, and the same technical effects can still be achieved, thereby achieving the ultimate technical purpose of the present invention.

[0041] In the following examples, dolomite powder is taken from Yu County, Yangquan, Shanxi Province, and has a blue light whiteness of 60-80; the proportions of the ingredients are: silicon dioxide 5% to 10%, calcium oxide 25% to 32%, magnesium oxide 15% to 21%, aluminum oxide less than 3%, iron oxide less than 1%, and acid insoluble matter 5 to 8%;

[0042] The chemical formula of the silane coupling agent is RSiX3. In the silane coupling agent used in the embodiments of the present application, R is a short-chain alkane and X is a halogen.

[0043] The weight of each coupling agent in the following examples is the weight of the purchased stock solution, which is used after being diluted 10 to 20 times with water; the weight of each dispersant is the weight of the purchased powder, which is used after being dissolved after adding water at a weight multiple of 1:15 to 1:20.

[0044] The particle size of the nano oxide is 1 to 100 nm.

[0045] Unless otherwise specified, all raw materials in this specification were purchased from commercial sources.

[0046] Embodiment 1:

[0047] In this embodiment, dolomite powder coated with nano-oxide is prepared from the following raw materials by weight:

[0048]

[0049] The method for preparing dolomite powder coated with nano-oxide provided in this embodiment specifically comprises the following steps:

[0050] (1) grinding dolomite powder by a vertical mill and then selecting ultrafine dolomite powder with a particle size of 800-1200 meshes by air separation; during the air separation, the passing rate of the dolomite powder through an 800-mesh sieve is 100%, the passing rate of the 950-mesh sieve is 75%±5%, the passing rate of the 1100-mesh sieve is 40%±5%, and the passing rate of the 1200-mesh sieve is less than 5%;

[0051] (2) adding water to dolomite powder, 86% of dispersant and coupling agent A, and dispersing at a high speed of 180,000 rpm for 50 min at a dispersion temperature not higher than 30° C. to prepare a dolomite powder suspension having a solid content of 20 wt %;

[0052] (3) adding water to the nano-oxide and the remaining dispersant, and dispersing at a high speed of 100,000 rpm for 45 min at a dispersion temperature not higher than 30° C. to prepare a nano-oxide suspension having a solid content of 25%;

[0053] (4) slowly pouring the coupling agent B diluted with water into the dolomite powder suspension, stirring at 700 rpm for 5 min, then slowly pouring the nano oxide suspension into it, stirring at 1300 rpm for 30 min, to prepare a mixed suspension;

[0054] (5) The mixed suspension obtained in step (4) is washed with water, filtered or centrifuged, washed with water, and centrifuged again, and then air-dried at a temperature below 35° C. to prepare dolomite powder coated with nano-oxide.

[0055] The dolomite powder coated with nano-oxide prepared in Example 1 has high purity, but a small amount of particles have slight agglomeration phenomenon, and is usually used as a filler in the preparation of artificial marble, plastic profiles, and wood composite panels.

[0056] Embodiment 2:

[0057] In this embodiment, the dolomite powder coated with nano-oxide is prepared from the following raw materials by weight:

[0058]

[0059] The difference between the preparation method in this embodiment and that in embodiment 1 is:

[0060] The drying method in step (5) is: the mixed suspension is atomized and dried at a temperature below 35°C.

[0061] The dolomite powder coated with nano-oxide prepared in Example 1 contains a small amount of dispersant and coupling agent that do not participate in the reaction, and has a relatively low purity. It is usually used as a filler in the preparation of putty powder, grout, and plaster mortar.

[0062] Embodiment 3:

[0063] The difference between this embodiment and embodiment 1 is that the dolomite powder coated with nano-oxide in this embodiment is prepared from the following raw materials by weight:

[0064]

[0065] Figure 1 The figure shows the coating model of nano-oxide particles on the surface of dolomite powder particles. Component A of the coupling agent forms micro-pits on the surface of dolomite particles through acid etching for the embedding of nano-oxides, thereby improving the bonding strength between the nano-oxides and the dolomite particles.

[0066] like Figure 2 As shown in the SEM image, in the present invention, the dolomite particles tend to be spherical after high-speed dispersion, and the surface morphology of the dolomite particles is significantly changed after the nano-oxide particles are coated on the surface of the dolomite particles. In addition, the nano-oxide has a high coating rate, which enables the nano-oxide to be evenly dispersed as a filler, and better exerts the anti-mildew and sterilization properties.

[0067] Adding the dolomite powder coated with nano-oxide provided by the present application to the putty powder for painting walls at a ratio of 3‰ to 3% can effectively inhibit the growth and spread of mold.

[0068] In order to verify the use effect of the dolomite powder coated with nano-oxide provided by the present invention, the present invention conducted the following anti-mildew test on Samples 1 to 3.

[0069] Sample 1: putty powder without any mildew inhibitor;

[0070] Sample 2: A mildew-proof putty powder sold on the market;

[0071] Sample 3: The dolomite powder coated with nano-oxide provided by the present invention is added to Sample 1 at a ratio of 1%.

[0072] According to GB / T 1741-2020 "Determination of mildew resistance of paint film", the mildew resistance test was carried out. Samples 1-3 were made into three groups of samples in the same way, recorded as putty block samples 1-3. Each group of samples contained three putty blocks, which were placed in nutrient salt agar medium, sprayed with 8 kinds of molds, and placed in a mold incubator with a temperature of 28°C and a humidity of not less than 85% for 28 days. The test results are as follows:

[0073] Putty block sample 1( Figure 3 ) The surface is obviously heavily contaminated by mold, with the pollution level reaching Level 4.

[0074] Putty block sample 2( Figure 4 ) The samples had obvious mold contamination, two of which reached level 4 mold contamination and one reached level 3 mold contamination.

[0075] Putty block sample 3( Figure 5 ) None of the samples were contaminated by mold.

[0076] Experiments have shown that putty block sample 3 can effectively resist the erosion of external microorganisms and bacteria, and can be widely used in interior decoration, especially in the decoration of children's rooms. It can effectively inhibit the growth and spread of wall mold in a humid environment.

[0077] The above specific implementation manner cannot be used as a limitation on the protection scope of the present invention. For those skilled in the art, any substitution, improvement or change made to the implementation manner of the present invention falls within the protection scope of the present invention.

[0078] The matters not described in detail in the present invention are all known technologies to those skilled in the art.

Claims

1. A method for preparing dolomite powder coated with nano-oxide, characterized in that: It is prepared by the following raw materials in weight percentage: 80% to 85% dolomite powder, 10% to 18% nano oxide, 1% to 5% coupling agent, and 0.5% to 1.5% dispersant; Wherein, the nano-oxide is selected from any one or more of copper oxide, zinc oxide, magnesium oxide, aluminum oxide, titanium oxide, and silver oxide; The coupling agent is composed of component A and component B, the weight ratio of component A to component B is 1:1 to 1:3, component A is selected from any one or two of stearic acid and malic acid, and component B is selected from any one or two of silane coupling agent and aluminate coupling agent; The dispersant is selected from one or both of gum arabic and sodium alkylbenzene sulfonate; The proportions of ingredients contained in dolomite powder are: silicon dioxide 5% to 10%, calcium oxide 25% to 32%, magnesium oxide 15 to 21%, aluminum oxide less than 3%, iron oxide less than 1%, and acid insoluble matter 5 to 8%; The method for preparing dolomite powder coated with nano-oxide comprises the following steps: (1) Grinding dolomite powder with a vertical mill and then selecting ultrafine dolomite powder with a particle size of 800 to 1200 mesh by air separation; (2) adding water to dolomite powder, part of the dispersant and component A, and dispersing them uniformly at high speed to prepare a dolomite powder suspension with a solid content of 20 to 30 wt%; (3) adding water to the nano-oxide and the remaining dispersant, and then dispersing them uniformly at high speed to prepare a nano-oxide suspension with a solid content of 20 to 30 wt%; (4) After adding water to the dolomite powder suspension, the nano oxide suspension and component B, the mixture is stirred at a low speed to obtain a mixed suspension, wherein the pH value of the mixed suspension is 6.5 to 7.5; (5) Drying the mixed suspension obtained in step (4) at a temperature below 35° C. to prepare dolomite powder coated with nano-oxide.

2. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: The blue light whiteness of the dolomite powder is 60-80.

3. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: The particle shape of dolomite powder is approximately spherical, olive-shaped or columnar; the particle size of dolomite powder is 800-1200 mesh; and the particle size of nano-oxide is 1-100 nm.

4. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: The dolomite powder is obtained from Yu County, Yangquan, Shanxi.

5. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: In step (1), during air separation, the pass rate of dolomite powder through 800 mesh sieve is 100%, the pass rate through 950 mesh sieve is 75%±5%, the pass rate through 1100 mesh sieve is 40%±5%, and the pass rate through 1200 mesh sieve is less than 5%.

6. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: In step (2), the dispersion speed when preparing the dolomite powder suspension is 150,000 to 200,000 rpm, the dispersion time is 30 to 60 min, and the dispersion temperature is not higher than 30°C.

7. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: In step (3), the dispersion speed when preparing the nano-oxide suspension is 80,000 to 120,000 rpm, the dispersion time is 30 to 60 min, and the dispersion temperature is not higher than 30°C.

8. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: In step (4), the dolomite powder suspension, the nano-oxide suspension and the component B are mixed by slowly pouring the component B into the dolomite powder suspension, stirring at a speed of 500 to 800 rpm for 5 min, and then slowly pouring the nano-oxide suspension, stirring at a speed of 1000 to 1500 rpm for 30 min.

9. The method for preparing dolomite powder coated with nano-oxide according to claim 1, characterized in that: When the dolomite powder coated with nano-oxide is used as a filler in the preparation of artificial marble, plastic profiles, and wood composite panels, the drying method in step (5) is: the mixed suspension is washed with water, filtered or centrifuged, washed with water, and then centrifuged, and then air-dried at a temperature below 35°C; When the dolomite powder coated with nano-oxide is used as a filler in the preparation of putty powder, grout, and plaster mortar, the drying method in step (5) is: the mixed suspension is atomized and dried at a temperature below 35°C.

Citation Information

Patent Citations

  • Method for preparing exterior wall coating for building from dispersant-modified multi-walled carbon nanotubes

    CN110698928A